Interstitial lung disease progression after genomic usual interstitial pneumonia testing. Issue 4 (3rd April 2023) - Chaudhary, Sachin; Weigt, S. Sam; Ribeiro Neto, Manuel L.; Benn, Bryan S.; Pugashetti, Janelle Vu; Keith, Rebecca; Chand, Arista; Oh, Scott; Kheir, Fayez; Ramalingam, Vijaya; Solomon, Joshua J.; Harper, Richart; et al.
Background: A genomic classifier for usual interstitial pneumonia (gUIP) has been shown to predict histological UIP with high specificity, increasing diagnostic confidence for idiopathic pulmonary fibrosis (IPF). Whether those with positive gUIP classification exhibit a progressive, IPF-like phenotype remains unknown. Methods: A pooled, retrospective analysis of patients who underwent clinically indicated diagnostic bronchoscopy with gUIP testing at seven academic medical centres across the USA was performed. We assessed the association between gUIP classification and 18-month progression-free survival (PFS) using Cox proportional hazards regression. PFS was defined as the time from gUIP testing to death from any cause, lung transplant, ≥10% relative decline in forced vital capacity (FVC) or censoring at the time of last available FVC measure. Longitudinal change in FVC was then compared between gUIP classification groups using a joint regression model. Results: Of 238 consecutive patients who underwent gUIP testing, 192 had available follow-up data and were included in the analysis, including 104 with positive gUIP classification and 88 with negative classification. In multivariable analysis, positive gUIP classification was associated with reduced PFS (hazard ratio 1.58, 95% CI 0.86–2.92; p=0.14), but this did not reach statistical significance. Mean annual change in FVC was −101.8 mL (95% CI −142.7– −60.9 mL; p<0.001) for those with positive gUIP classification and −73.2 mL (95% CI −115.2– −31.1 mL; p<0.001) for those with negative classification (difference 28.7 mL, 95% CI −83.2–25.9 mL; p=0.30). Conclusions: gUIP classification was not associated with differential rates of PFS or longitudinal FVC decline in a multicentre interstitial lung disease cohort undergoing bronchoscopy as part of the diagnostic evaluation. While genomic UIP classification is not associated with categorical ILD progression, it is associated with modestly higher 1-year rate of FVC decline http://bit.ly/3ii99Gb